VALIDITY AND PRACTICALITY OF ANIMATION VIDEO-BASED LEARNING MEDIA ON VARIOUS FORCES AND INERTIAL PROPERTIES OF OBJECTS - Fajriati, Dwi Yunita; Putra, Amali (Department of Physics Universitas Negeri Padang, 2023)
Contextual learning using observation objects about natural properties and phenomena in learning physics still finds many obstacles. Such as the lack of laboratory facilities, demonstration equipment and direct observations in the field. So we need learning media that can show real conditions, namely animated videos. In the concept of force and inertial properties of objects, there are difficulties in describing forces proportionally and describing forces in free diagrams which have an impact on difficulties answering questions in quantitative or qualitative terms. This study aims to determine the characteristics and produce valid and practical animated video-based learning media. This development research uses the Plomp model which is limited to the development stage (one to one evaluation). The research instruments used were journal analysis sheets, teacher interviews, self-evaluation sheets, material expert and media expert validation sheets, and one to one evaluation assessment sheets. Preliminary research analysis techniques using descriptive analysis techniques. While the development stage uses the percentage technique. The results of the journal analysis showed that it was difficult to learn the concept of style and the inertia of objects. In the teacher interviews, it was shown that learning in the classroom was still saturated due to the lack of variations in graphical learning media. At the development stage the results of the self-evaluation test obtained very good criteria, on the expert review test the validation results were obtained by material experts 81% and 93.8%. While the practicality stage obtained results by teachers 87.9% and 86.9% by students. So, the animated video media is valid and practical so that it can be continued at the effectiveness test stage.